Analisis Model UTAUT (Unified Theory Of And Use Of Technology Syaria) Pada Pengguna Qris di Kota Semarang - Rahmawati Idha Wibowo (Jurnal Ilmiah Ekonomi Islam, 2023)
Technological development in Indonesia is currently providing convenience for doing transactions especially in big cities. The aim of this research is to analyze the application of UTAUT (Unified Theory of Acceptance and Use of Technology) Model in order to improve positive attitude and behavioral intention to use QRIS as transaction tool. The total of sample used on this research is 239 samples and analyzed using SEM (Structural Equation Modeling) technique. The result of this study shows that Performance Expectancy, Effort Expectancy and Facilitating Condition have significant effect toward Attitude. Effort Expectancy and Facilitating Condition also have significant effect on Behavior Intention to use QRIS, meanwhile Performance Expectancy does not have significant effect on Behavioral Intention. Attitude gives significant effect on Behavioral Intention and also mediate the impact of Performance Expectancy, Effort Expectancy, and Facilitating Conditions on Behavior Intention to use QRIS for Transaction.